2001
DOI: 10.1046/j.1365-8711.2001.04186.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of accretion discs threaded by a strong magnetic field

Abstract: We study the stability of poloidal magnetic fields anchored in a thin accretion disc. The two-dimensional hydrodynamics in the disc plane is followed by a grid-based numerical simulation including the vertically integrated magnetic forces. The 3--dimensional magnetic field outside the disc is calculated in a potential field approximation from the magnetic flux density distribution in the disc. For uniformly rotating discs we confirm numerically the existence of the interchange instability as predicted by Sprui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…The magnetic field is, therefore, the essential feature of the model and the equations do not change to standard α-disk equations in the low field limit. The existence of magnetic-induced accretion is also confirmed by the results of Stehle & Spruit (2001). Our results actually demonstrate the close relation between magnetic field dragging and the vertical structure of thin accretion disks.…”
Section: Discussionsupporting
confidence: 83%
“…The magnetic field is, therefore, the essential feature of the model and the equations do not change to standard α-disk equations in the low field limit. The existence of magnetic-induced accretion is also confirmed by the results of Stehle & Spruit (2001). Our results actually demonstrate the close relation between magnetic field dragging and the vertical structure of thin accretion disks.…”
Section: Discussionsupporting
confidence: 83%
“…In such a subcritical cloud, force balance along the field lines is achieved during the quasi-static phase of evolution and is well maintained even during the subsequent dynamic collapse (e.g., Fiedler & Mouschovias 1993;Nakamura, Hanawa, & Nakano 1995). Thus, we adopt the standard thin-disk approximation in which exact force balance along the vertical direction is assumed during the entire evolution (e.g., Ciolek & Mouschovias 1993;Basu & Mouschovias 1994;Li & Shu 1996;Nakamura & Hanawa 1997;Stehle & Spruit 2001;Li 1999). The MHD equations are integrated in the vertical direction, and the cloud evolution is followed in the (x-y) disk plane of a Cartesian coordinate system ðx; y; zÞ with a two-dimensional MHD code.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Though the origin of such fields is not as clear as the turbulent fields that evolve from initially weak seed fields, they are by far the most logical configurations for producing systematic outflows from accretion disks. Spruit et al (1995), Stehle (1997) and Stehle & Spruit (2001) have shown that even surprisingly strong poloidal fields, approaching (a fraction of) equipartition with orbital kinetic energy, can still be stably anchored in a disk. These analyses did not include instabilities associated with magnetically driven outflows however, which are the subject of the present study.…”
Section: Modelmentioning
confidence: 99%